Food Policy: Its Role in Price Stability and Food Security - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1997)
Due to the increase in prices of basic agricultural commodities in 1995, food price stability and food security have again emerged as a major policy concern. This paper argues that the sharp increases in prices of rice; largely the choice and management of policy instrument have caused corn and sugar. Highly protectionist policy on tariffs imposed on sensitive agricultural products is not sustainable over a prolonged period of time. Moreover, bidding out of the right to import while retaining quotas, can minimize gross errors in timing and amount of importation.
Keywords: 330; food sector; food price stability; nominal protection rate; price instability